2021
DOI: 10.1371/journal.pone.0259022
|View full text |Cite
|
Sign up to set email alerts
|

Nest survival of Seaside Sparrows (Ammospiza maritima) in the wake of the Deepwater Horizon oil spill

Abstract: In 2010, the Deepwater Horizon oil spill released an estimated 4.9 million barrels of oil into the Gulf of Mexico, damaging coastal ecosystems. Seaside Sparrows (Ammospiza maritima)—a year-round resident of Gulf Coast salt marshes—were exposed to oil, as shown by published isotopic and molecular analyses, but fitness consequences have not been clarified. We monitored nests around two bays in Plaquemines Parish, Louisiana, USA from 2012–2017 to assess possible impacts on the nesting biology of Seaside Sparrows.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…Study plots (25 ha; 50 × 500 m along marsh edge) were established in areas initially oiled ( n = 4) and areas not initially impacted ( n = 3) by the Deepwater Horizon event. Nests were found as part of a study examining nest survival following the oil spill; nest search effort was equal across plots within years (Hart et al 2021).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Study plots (25 ha; 50 × 500 m along marsh edge) were established in areas initially oiled ( n = 4) and areas not initially impacted ( n = 3) by the Deepwater Horizon event. Nests were found as part of a study examining nest survival following the oil spill; nest search effort was equal across plots within years (Hart et al 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Predation pressure may also influence EPP (e.g., Teru and Itsuro 2016, Abbey-Lee et al 2018). In our study area, Seaside Sparrow nest survival is higher in more sheltered contexts (Hart et al 2021), so we asked if EPP was less prevalent in our more sheltered sites. Statistical tests were performed in R 4.1.1 (R Core Team 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Site‐level vegetation data were collected as part of another, concurrent study (Hart et al, 2021); GoMRI https://doi.org/10.7266/n7-w5g6-e664). Ground cover was quantified for a 5 m radius around randomly selected points ( n = 200; total).…”
Section: Methodsmentioning
confidence: 99%
“…A principal component analysis (PCA) was first used to evaluate structure in ground cover characteristics ( ggbiplot; Vu, 2011). Based on the results of the PCA (Figure 2) and Hart et al (2021), which found substantial overlap in PCA space for vegetation  treatment, it was more informative to investigate the site-specific relationship between ground cover characteristics and prevalence rather than group data points by treatment. The mean plot scores of PC1 and PC2 (Fischer et al, 2018;Kitagawa et al, 2020) for each site were used in analyses (described below) to evaluate whether prevalence was related to a site's ground cover characteristics.…”
Section: Habitat Datamentioning
confidence: 99%